Pengaruh koneksitas organ corporate governance, ineffective monitoring dan manajemen laba terhadap fraudulent financial reporting - Oriza Zea Sabrina; Fachruzzaman Fachruzzaman; Pratana Puspa Midiastuty; Eddy Suranta (Penerbit Goodwood, 2020)
Purpose: This study aims to provide empirical evidence of the Effect of Organ Connectivity in Corporate Governance, Effective Monitoring, and Earnings Management on Fraudulent Financial Reporting on non-financial companies listed on the Indonesia Stock Exchange with an observation period from 2010-2018. Research methodology: The measurement of corporate governance organ connectivity used dummy variables. Effective monitoring used the proportion of independent commissioners to the number of boards. The Modified Jones model was used to Measure earnings management. The cheating prediction model used the combination of Beneish M-Score and Altman Z-Score. Results: Corporate governance organs that have political connections and ineffective monitoring have no effect on fraudulent financial reporting, while earnings management has an effect on fraudulent financial reporting. The practice of earnings management carried out by companies is not caused by the company's motivation to carry out fraudulent financial reporting. Limitation: The limitations of this study are due to the use of logistic regression by using a combined model of Beneish M-Score and Altman Z-Score still found type I and type II errors. The research variables can only explain the fraudulent financial reporting of 24.7% and is less precise in determining the category of companies that have political connections or not. Contribution: This research provides an overview and understanding as a reference for stakeholders in the detection of fraudulent financial statements and for further research. Keywords: Fraudulent financial reporting, Independent commissioner, Independent director, Audit committee, Ineffective monitoring, Earnings management